A constituição de um território identitário pela garantia dos direitos fundiários: o Sítio Histórico e Patrimônio Cultural Kalunga / The constitution of a identity territory for warranty of land rights: The Historic and Cultural Site Kalunga - Luana Nunes Martins de Lima (Revista Sociedade & Natureza, 2013)
The article discusses the constitution of Historic and Cultural Site Kalunga, situated in the north of Goiás, making considerations about the communities it distributed in, the form of occupation in Cerrado of Goiás and the official recognition of its territory. Presents a discussion about how the discourses of identity self-assertion and the patrimonialization of quilombolas territory modify the reproductive strategies of these groups. This process, however, only occurs by external interference that works in raising awareness of these communities in relation to their constitutional rights. Before the need of self-assertion, the discourse of identity resignify the meaning of these communities struggle: the right to land. Finally, it detach the problem regarding community title of land property. These issues are discussed through a literature review that permeated the theme, observations and interviews made on the spot. Preliminarily, there are some conclusions that point to the need to rethink the policies that prioritize the cultural preservation directed to the quilombolas communities, rather than their actual demands.